Association of 24-Hour In-house Neonatologist Coverage with Outcomes of Extremely Preterm Infants - Debay, Anthony; Shah, Prakesh; Lodha, Abhay; Shivananda, Sandesh; Redpath, Stephanie; Seshia, Mary; Dorling, Jon; Lapointe, Anie; Canning, Rody; Strueby, Lannae; Beltempo, Marc; on behalf of the Canadian Neonatal Network Investigators (American Journal of Perinatology, 2022)
Objective This study aimed to assess if 24-hour in-house neonatologist (NN) coverage is associated with delivery room (DR) resuscitation/stabilization and outcomes among inborn infants <29 weeks' gestational age (GA).Study design Survey-linked cohort study of 2,476 inborn infants of 23 to 28 weeks' gestation, admitted between 2014 and 2015 to Canadian Neonatal Network Level-3 neonatal intensive care units (NICUs) with a maternity unit. Exposures were classified using survey responses based on the most senior provider offering 24-hour in-house coverage: NN, fellow, and no NN/fellow. Primary outcome was death and/or major morbidity (bronchopulmonary dysplasia, severe neurological injury, late-onset sepsis, necrotizing enterocolitis, and retinopathy of prematurity). Multivariable logistic regression analysis was used to assess the association between exposures and outcomes and adjust for confounders.Results Among the 28 participating NICUs, most senior providers ensuring 24-hour in-house coverage were NN (32%, 9/28), fellows (39%, 11/28), and no NN/fellow (29%, 8/28). No NN/fellow coverage and 24-hour fellow coverage were associated with higher odds of infants receiving DR chest compressions/epinephrine compared with 24-hour NN coverage (adjusted odds ratio [aOR] = 4.72, 95% confidence interval [CI]: 2.12–10.6 and aOR = 3.33, 95% CI: 1.44–7.70, respectively). Rates of mortality/major morbidity did not differ significantly among the three groups: NN, 63% (249/395 infants); fellow, 64% (1092/1700 infants); no NN/fellow, 70% (266/381 infants).Conclusion 24-hour in-house NN coverage was associated with lower rates of DR chest compressions/epinephrine. There was no difference in neonatal outcomes based on type of coverage; however, further studies are needed as ecological fallacy cannot be ruled out.Key Points
Keywords: prematurity; coverage; neonatal intensive care unit; resuscitation; delivery room; cardiopulmonary resuscitation; neonatologist